Pelatihan dan Pendampingan Literasi Etika Digital Berbasis Nilai Religius bagi Guru di SMP Muhammadiyah Al Mujahidin - Junaidi Junaidi; Nurbayti Nurbayti; Zahrotus Sa'idah; Ahmad Ridwan (Jurnal Riset Pendidikan Multidisiplin dan Pengabdian Kepada Masyarakat, 2026)
In the era of digital disruption, teachers are required not only to have pedagogical competence but also to demonstrate social piety in their cyber behavior. However, phenomena show that the educational environment is still vulnerable to cyberbullying practices and digital ethical violations, both those that place educators as victims or unintentionally as perpetrators. Based on an initial survey at Muhammadiyah Al Mujahidin Middle School, 45% of teachers had been involved in toxic debates in WhatsApp groups, 60% did not understand the limits of the ITE Law, and 30% experienced mental anxiety due to the pressure of social media interactions. This condition indicates a disconnection between religious identity in the real world and digital identity. This service aims to transform teachers' social piety through digital ethical literacy based on religious values. The implementation method uses a Participatory Technology Development approach through four stages: (1) Socialization of "Digital Taqwa", (2) Ethics Literacy and Anti-Cyberbullying Workshop, (3) Implementation of Bully Alert, and (4) Clinical mentoring and evaluation. The results of the community service demonstrated a significant increase in participants' understanding of digital ethical literacy, from 35% to 82%, based on a post-test. Furthermore, the formation of internal "Digital Piety Ambassadors" and the drafting of a School Digital Ethics Standard Operating Procedure (SOP) are sustainable outcomes of the program. In conclusion, the integration of religious values ​​into digital literacy education effectively reduces toxic cyber behavior and strengthens teachers' character as role models in the digital space.